Bibliometric analysis of research in genetic and anterior cruciate ligament rupture in sport: A review - Arroyo Moya, Wilson (2024)
Introduction: Genetic component has been established as a significant risk factor for anterior cruciate ligament rupture (ACLR). Current research has focused on knowing the candidate genes that can influence and predispose a subject to this injury. Objective: A bibliometric analysis was carried out to trace the results of the research and identify global trends and gaps in knowledge about the relationship between the genetic component and ACLR. Methodology: Data were extracted from the Pubmed and Scopus databases and analyzed in the Bibliometrix package of the R software. A total of 63 studies published since 2007 were identified. Results: Most of the publications recovered were research articles (85.71%). The authors with the highest number of those are in Poland and South Africa. The analysis through the co-occurrence map reveals that there is a mainline of research based on the study of genetic polymorphisms, especially in the genes of the collagen families (COL1A1, COL5A1, COL12A1, in greater frequency). A total of 54 candidate genes were identified within the studies. Conclusion: We hope that this study can help to find key points and research gaps by providing a comprehensive analysis and structured information on this topic.